The impact of green marketing of food and beverages on consumers' purchase intention - Yong, Xin En (2024)
Green marketing is helpful in affecting the consumers’ purchase intention to encourage actual purchase. It is essential to study how the green marketing of F&B would have effect on the purchase intention of consumers to address the environmental issues effectively. The objective of this study is to determine the factors of green marketing which would affect the consumers’ purchase intention in the F&B sectors.